Agri-food by-products as a source of sustainable ingredients for the production of functional foods and nutraceuticals - Ivanović, Nevena; Ilić, Tijana; Zrnić Ćirić, Milica; Todorović, Vanja; Djuričić, Ivana; Dabetić, Nevena (Archives of Pharmacy, 2023)
The disposal of waste generated in the agri-food industry is one of the greatest challenges in achieving sustainable development. Although agri-food residues are a potential source of bioactive compounds with proven health benefits, they are largely unused and disposed of as organic waste. The recovery of bioactive compounds from agri-food waste to obtain products with high biological value, such as functional foods and nutraceuticals, is an idea that stems from the concept of bioeconomy and combines environmental issues with economically viable production. Some of the main agri-food wastes in Serbia that have the potential to be recycled into value-added products are apple, plum, grape, tomato, and beet pomace, and oilseed cakes. Bioactive compounds isolated from these wastes include polyphenols, fibers, essential fatty acids, minerals, various volatiles and pigments. This article focuses on the most common food wastes and the potential reuse of these undervalued material to produce value-added products such as functional foods, nutraceuticals or food additives.